Strategi Pengembangan Industri Rumah Tangga-Usaha Mikro (IRT-UM) Annisa 36 dan Bandeng Presto Pandean di Kota Semarang dalam Menciptakan Keungggulan Kompetitif - Sulistyo, Heru; Gunarto, Gunarto; Anik, Sri; Adi, Henny Pratiwi; Adiwijaya, Zainal Alim; Saputri, Pungky Lela (Indonesian Journal of Community Services, 2025)
Industri Rumah Tangga Annisa 36 Semarang, yang berdiri sejak 17 Agustus 2023, memproduksi berbagai makanan seperti kentang mustofa, peyek, dan kue kering. Sementara itu, IRT Bandeng Presto Pandean, berdiri sejak Maret 2015 di Pandean Lamper, Kota Semarang, fokus pada produk bandeng seperti bandeng presto, otak-otak, pepes, nugget, bakso, dan sate bandeng sebagai oleh-oleh khas Semarang. Permasalahan yang dihadapi kedua IRT-UM adalah bagaimana mengembangkan usaha agar kompetitif. Kajian dilakukan menggunakan analisis SWOT, meliputi kekuatan, kelemahan, peluang, dan ancaman pada aspek keuangan, sumber daya manusia, produksi, pemasaran, dan promosi. Hasil analisis dikembangkan dalam matriks SWOT yang menawarkan empat strategi utama: SO (Strength-Opportunity), WO (Weakness-Opportunity), ST (Strength-Threat), dan WT (Weakness-Threat). Strategi yang dipilih disesuaikan dengan kondisi masing-masing IRT-UM dan bergantung pada keputusan pemilik usaha. Pendekatan ini bertujuan membantu Annisa 36 dan Bandeng Presto Pandean meningkatkan daya saing dan menciptakan keunggulan kompetitif dalam industri pangan lokal.Annisa 36 Home Industry, established on August 17, 2023, in Candi Losmen, Semarang City, produces various food items such as crispy fried potatoes (kentang mustofa), traditional crackers (peyek), and assorted cookies. Meanwhile, Bandeng Presto Pandean Home Industry, founded in March 2015 in Pandean Lamper, Semarang City, specializes in milkfish-based products, including bandeng presto, milkfish otak-otak, steamed milkfish (pepes), milkfish nuggets, milkfish meatballs, and milkfish satay, making it a prominent producer of Semarang's signature food souvenirs. The main challenge faced by these two micro-enterprises (IRT-UM) is how to develop their businesses to remain competitive. The study utilizes a SWOT analysis framework, which examines internal conditions (strengths and weaknesses) and external factors (opportunities and threats) across financial, human resources, production, marketing, and promotional aspects. The results are structured into a SWOT matrix offering four primary business strategies: Strength-Opportunity (SO), Weakness-Opportunity (WO), Strength-Threat (ST), and Weakness-Threat (WT). The strategy selection is tailored to the unique conditions of each home industry and depends significantly on the decision-making of the respective business owners. This approach aims to assist Annisa 36 and Bandeng Presto Pandean in enhancing their competitiveness and establishing a sustainable edge within the local food industry.